Qualitative findings on the use of mobile phones by Malaysian older people - Abd. Malik, Sofianiza; Azuddin, Muna (IEEE Computer Society, 2013)
This paper reports on qualitative findings that have been obtained from a study about mobile phone usage by Malaysian older people. The information has been classified into various categories such as usage, difficulties encountered with the physical interface of the mobile phone, functions complexity, cost, language related issues, ideal phone and etc. In this study, two similar experiments were carried out that focus on focus groups. In addition, the use of personas as a tool in elicitation was explored. Mobile phones can potentially play an important role in helping older people in many ways if the problems related to the use of mobile phone can be solved. It is customer product that relates to theories of identity, culture and social structure. The findings presented in this paper may have implications for the design of mobile phones in general. It may be concluded that the usability of current mobile phones has to be enhanced in order to cater the needs of other groups of users, including older people.